Transition-Metal-Doping of CaO as Catalyst for the OCM Reaction, a Reality Check - Thum, Lukas; Riedel, Wiebke; Milojevic, Natasa; Guan, Chengyue; Trunschke, Annette; Dinse, Klaus-Peter; Risse, Thomas; Schomäcker, Reinhard; Schlögl, Robert (Frontiers in Chemistry, 2022)
In this study, first-row transition metal-doped calcium oxide materials (0.1 atom% Mn, Ni, Cr, Co, and Zn) were synthesized, characterized, and tested for the OCM reaction. Doped carbonate precursors were prepared by a co-precipitation method. The synthesis parameters were optimized to yield materials with a pure calcite phase, which was verified by XRD. EPR measurements on the doped CaO materials indicate a successful substitution of Ca2+ with transition metal ions in the CaO lattice. The materials were tested for their performance in the OCM reaction, where a beneficial effect towards selectivity and activity effect could be observed for Mn-, Ni-, and Zn-doped samples, where the selectivity of Co- and Cr-doped CaO was strongly reduced. The optimum doping concentration could be identified in the range of 0.04-0.10 atom%, showing the strongest decrease in the apparent activation energy, as well as the maximum increase in selectivity. The overall improvement of the catalyst though was only minor and limited.